A production process of HDPE composite antistatic gasket
By mixing HDPE with conductive fillers, short fibers, coconut oil and other materials, and extruding and granulating them in a screw extruder, HDPE composite anti-static gaskets are prepared, which solves the problem of static electricity accumulation during use of HDPE gaskets. problem, achieving excellent anti-static and mechanical properties.
Patent Information
- Application Number
- CN202410562302.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The existing HDPE gasket raw materials are prone to static accumulation during use, resulting in potential dangers such as vacuuming, electric shock and spark explosion.
HDPE composite anti-static gaskets are prepared by mixing HDPE with materials such as conductive fillers, short fibers and coconut oil, and extruding and granulating them in a screw extruder. This process gives the material excellent conductive properties by adding conductive fillers and effectively eliminates static electricity.
It achieves the excellent anti-static and mechanical properties of HDPE composite gaskets, avoids potential safety hazards caused by static electricity accumulation, and improves the safety of the material.
Smart Images

Figure CN118325147B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene resins, and in particular to a production process of a HDPE composite antistatic gasket. Background Art
[0002] Glass bottles are an important packaging container. With the increasing diversification of people's needs, more and more product packaging has begun to return to the use of glass bottles. Glass bottles are mainly used to package liquids, solid medicines and liquid beverages. As one of the main packaging materials, glass has excellent transparency, gas barrier properties and chemical stability, and can be recycled; but it also has its defects such as fragility, heavy volume and large volume, and is easy to break during transportation. At present, the most widely used and most effective transportation packaging method in actual production is the pallet container method. Plastic gaskets are used as containers for holding and transporting glass products in the pallet container method. They have the advantages of being light, stable, beautiful, good integrity, no nails and thorns, tasteless and non-toxic, acid-resistant, alkali-resistant, corrosion-resistant, easy to rinse and disinfect, non-rotten, and recyclable. They are important tools for modern transportation, packaging, and warehousing.
[0003] High-density polyethylene (HDPE) and polypropylene (PP) are the two main raw materials for the production of plastic gaskets. PP has high mechanical strength and deformation resistance, and its shrinkage rate is smaller than that of HDPE. However, due to the presence of side methyl groups, the flexibility of the molecular chain is worse than that of HDPE, and thus its low-temperature toughness is worse than that of HDPE. HDPE has a regular structure, low macromolecular chain branching, and a crystallinity of up to 80-90%. Compared with PP, it has better impact resistance and excellent weather resistance. However, HDPE has a fast crystallization rate and high crystallinity. During the injection process, it has a large degree of orientation along the flow direction. When producing large flat products, there is a large warping deformation after demolding, which affects the surface quality and use of the products. Moreover, HDPE is a non-polar molecular structure. The molecular chain composed of its covalent bonds can neither store nor transfer free electrons. Once the electrons are gained or lost due to friction, it is difficult to eliminate them. Static electricity accumulates during use, which can easily cause dust absorption, electric shock, and even spark explosion accidents, making plastic gaskets potentially dangerous during use. Summary of the invention
[0004] The purpose of the present invention is to provide a production process of HDPE composite antistatic gasket to solve the following technical problems:
[0005] The existing HDPE gasket raw materials are polymer materials, which are prone to static electricity accumulation during use, causing dust absorption, electric shock, and even sparks and explosions, making plastic gaskets potentially dangerous during use.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A production process of a HDPE composite antistatic gasket comprises the following steps:
[0008] A1: HDPE, conductive filler, short fiber and coconut acid are mixed evenly and added into a screw extruder for extrusion and granulation to obtain a mixture 1;
[0009] A2: The conductive filler and HDPE are mixed evenly and then added into a screw extruder for extrusion and granulation to obtain a mixture II;
[0010] A3: Mix the mixture 1 and the mixture 2, and perform injection molding to obtain a HDPE composite antistatic gasket.
[0011] As a further solution of the present invention: Mixture 1 includes the following raw materials in weight percentage: 15-25% conductive filler, 15-20% short fiber, 5-10% coconut oil acid, and the balance is HDPE, and the sum of the weight percentages of the raw material components is 100%; the short fiber is silicate nano short fiber.
[0012] As a further solution of the present invention: Mixture 2 includes the following raw materials in weight percentage: 30-40% conductive filler, 60-70% HDPE, and the sum of the weight percentages of the raw material components is 100%.
[0013] As a further solution of the present invention: the mass ratio of the first mixture to the second mixture is 1:1-1.5.
[0014] As a further solution of the present invention: the preparation method of the conductive filler comprises the following steps:
[0015] S1: In a nitrogen atmosphere, 1,3,5-triethynylbenzene, 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), tetrakis(triphenylphosphine)palladium(0), cuprous iodide(Ⅰ), triethylamine and N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 70-80°C, the reaction was kept warm for 48-72h, and the mixture was washed and dried to obtain component 1;
[0016] S2: Add component 1, iodobenzene diacetate, phthalonitrile and dichloromethane into reactor B and disperse evenly, control the temperature to 70-80°C, keep warm for 24-48h, wash, dry and calcine to obtain component 2;
[0017] S3: Add component 2, hydroxylamine hydrochloride, triethylamine and anhydrous ethanol into reactor C and disperse them evenly. Control the temperature at 60-70°C, keep the temperature for reaction for 24-48 hours, remove ethanol by rotary evaporation, add dichloromethane and water for liquid extraction, remove dichloromethane by vacuum distillation, and dry to obtain component 3;
[0018] S4: Add component three, sodium hydroxide aqueous solution, 1,3-propane sultone and 1,4-dioxane into reaction kettle D, stir at room temperature for 12-18 hours, wash with acetone to obtain a conductive filler.
[0019] As a further scheme of the present invention: the addition ratio of 1,3,5-triethynylbenzene, 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), tetrakis(triphenylphosphine)palladium(0), cuprous iodide(I), triethylamine, and N,N-dimethylformamide in S1 is 1 g: 1.5-2 g: 0.2-0.4 g: 0.05-0.15 g: 50-100 mL: 50-100 mL.
[0020] As a further solution of the present invention: the addition ratio of component 1, iodobenzene diacetate, phthalonitrile, and dichloromethane in S2 is 1 g: 0.4-0.8 g: 0.2-0.5 mL: 10-50 mL.
[0021] As a further solution of the present invention: the addition ratio of component 2, hydroxylamine hydrochloride, triethylamine and anhydrous ethanol in S3 is 1g: 0.2-0.3g: 0.03-0.05g: 10-50mL.
[0022] As a further embodiment of the present invention: the sodium hydroxide aqueous solution in S4 is 0.8-1 g / mL sodium hydroxide aqueous solution; the addition ratio of component three, sodium hydroxide aqueous solution, 1,3-propane sultone, and 1,4-dioxane is 1 g: 7-15 mL: 2-3 g: 10-20 g.
[0023] As a further solution of the present invention: the extrusion temperature in A1 is 200-210°C; the extrusion temperature in A2 is 200-210°C; the temperatures of each section of the injection molding machine in A3 are: the temperature of zone 1 is 190-200°C, the temperature of zone 2 is 200-210°C, and the temperature of zone 3 is 210-220°C.
[0024] As a further scheme of the present invention: the specific steps of calcination in S2 are: the washed material is mixed with KOH in a mass ratio of 1:3, ground and loaded into a quartz boat, heated to 600°C in a nitrogen-filled tubular furnace at a heating rate of 5°C / min and kept warm for 3h, washed and dried to obtain component two.
[0025] Beneficial effects of the present invention:
[0026] The present application first uses 1,3,5-triethynylbenzene as a building unit and 2,5-dibromo-1,4-difluorobenzene as a linking unit, based on the Sonogashira coupling reaction, to prepare component one, which is a fluorine-doped porous polymer, and then the alkynyl group is modified to obtain a porous organic polymer rich in cyano groups, and it is used as a precursor, and KOH is used as an activator to calcine to obtain component two; component two prepared in the present application has a high specific surface area and an excellent hierarchical porous structure, as well as rich N and F doping, showing excellent conductive properties. The present application then uses component two as a matrix, triethylamine and hydroxylamine hydrochloride as reactants, and ethanol as a solvent, and converts the cyano group of component two into an amidoxime group through an amidoximation reaction to prepare component three; finally, the hydroxyl group on component three is used to open the ring with 1,3-propane sultone, and a sodium sulfonate group is grafted on component three to obtain a conductive filler.
[0027] The conductive filler prepared in the present application is a fluorine- and nitrogen-doped porous polymer as a matrix, and a large number of polar groups such as amino groups and hydroxyl groups are grafted on its surface through organic modification, which not only makes the conductive filler and the resin matrix compatible; but also adds conductive fillers and short fibers to the resin matrix, giving the material excellent conductive properties and mechanical properties. The polar matrix grafted on the surface of the conductive filler is adsorbed on the plastic surface through van der Waals force, and the hydrophilic polar groups extend outward to form a directional adsorption film of surfactant on the plastic surface to play a conductive role, so that static charges can be well dissipated; at the same time, the adsorption film can also play a good role in alleviating the friction of the plastic surface, giving the material excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] Figure 1 It is the production process flow chart of this application. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] The preparation method of the conductive filler comprises the following steps:
[0033] S1: In a nitrogen atmosphere, 100 g of 1,3,5-triethynylbenzene, 150 g of 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), 20 g of tetrakis(triphenylphosphine)palladium(0), 5 g of cuprous iodide(Ⅰ), 5000 mL of triethylamine and 5000 mL of N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 70°C, the reaction was kept warm for 48 h, and the component 1 was obtained by washing and drying.
[0034] S2: Add 100g of component 1, 40g of iodobenzene diacetate, 20mL of phthalonitrile and 1000mL of dichloromethane into reactor B and disperse them evenly. Control the temperature to 70°C, keep the temperature for 24h, wash and dry to obtain the washed substance. Mix the washed substance with KOH in a mass ratio of 1:3 and grind it into a quartz boat. In a nitrogen-filled tubular furnace, heat it up to 600°C at a rate of 5°C / min and keep the temperature for 3h. Wash and dry to obtain component 2.
[0035] S3: Add 100g of component 2, 20g of hydroxylamine hydrochloride, 3g of triethylamine and 2000mL of anhydrous ethanol into reactor C and disperse them evenly. Control the temperature at 60°C and keep the reaction for 24h. Remove the ethanol by rotary evaporation. Add dichloromethane and water for liquid extraction. Remove the dichloromethane by vacuum distillation and dry to obtain component 3.
[0036] S4: Add 50 g of component 3, 500 mL of 1 g / mL sodium hydroxide aqueous solution, 100 g of 1,3-propane sultone, and 500 g of 1,4-dioxane into reactor D, stir at room temperature for 12 h, and wash with acetone to obtain a conductive filler.
[0037] Example 2
[0038] The preparation method of the conductive filler comprises the following steps:
[0039] S1: In a nitrogen atmosphere, 100 g of 1,3,5-triethynylbenzene, 180 g of 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), 30 g of tetrakis(triphenylphosphine)palladium(0), 10 g of cuprous iodide(Ⅰ), 5000 mL of triethylamine and 5000 mL of N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 75°C, the reaction was kept warm for 60 h, and the mixture was washed and dried to obtain component 1;
[0040] S2: Add 100g of component 1, 60g of iodobenzene diacetate, 35mL of benzonitrile and 1000mL of dichloromethane into reactor B and disperse them evenly. Control the temperature to 75°C, keep the temperature for 36 hours, wash and dry to obtain the washed substance. Mix the washed substance with KOH in a mass ratio of 1:3 and grind it into a quartz boat. In a nitrogen-filled tubular furnace, heat it at a rate of 5°C / min to 600°C and keep the temperature for 3 hours. Wash and dry to obtain component 2.
[0041] S3: Add 100g of component 2, 25g of hydroxylamine hydrochloride, 4g of triethylamine and 2000mL of anhydrous ethanol into reactor C and disperse them evenly. Control the temperature at 65°C and keep the reaction for 36h. Rotary evaporate to remove ethanol. Add dichloromethane and water for liquid extraction. Remove dichloromethane by vacuum distillation and dry to obtain component 3.
[0042] S4: Add 50 g of component 3, 500 mL of 1 g / mL sodium hydroxide aqueous solution, 120 g of 1,3-propane sultone, and 800 g of 1,4-dioxane into reactor D, stir at room temperature for 15 h, and wash with acetone to obtain a conductive filler.
[0043] Example 3
[0044] The preparation method of the conductive filler comprises the following steps:
[0045] S1: In a nitrogen atmosphere, 100 g of 1,3,5-triethynylbenzene, 200 g of 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), 40 g of tetrakis(triphenylphosphine)palladium(0), 15 g of cuprous iodide(Ⅰ), 5000 mL of triethylamine and 5000 mL of N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 80°C, the reaction was kept warm for 72 h, and then washed and dried to obtain component 1;
[0046] S2: Add 100g of component 1, 80g of iodobenzene diacetate, 50mL of phthalonitrile and 1000mL of dichloromethane into reactor B and disperse them evenly. Control the temperature to 80°C, keep the temperature for 48h, wash and dry to obtain the washed substance. Mix the washed substance with KOH in a mass ratio of 1:3, grind it and put it into a quartz boat. In a nitrogen-filled tubular furnace, heat it at a rate of 5°C / min to 600°C and keep the temperature for 3h. Wash and dry it to obtain component 2.
[0047] S3: Add 100g of component 2, 30g of hydroxylamine hydrochloride, 5g of triethylamine and 2000mL of anhydrous ethanol into reactor C and disperse them evenly. Control the temperature to 70°C and keep the reaction for 48h. Remove the ethanol by rotary evaporation. Add dichloromethane and water for liquid extraction. Remove the dichloromethane by vacuum distillation and dry to obtain component 3.
[0048] S4: Add 50 g of component 3, 500 mL of 1 g / mL sodium hydroxide aqueous solution, 150 g of 1,3-propane sultone, and 1000 g of 1,4-dioxane into reactor D, stir at room temperature for 18 h, and wash with acetone to obtain a conductive filler.
[0049] Example 4
[0050] See also Figure 1, a production process of HDPE composite antistatic gasket, comprising the following steps:
[0051] A1: 55 g of HDPE (HDPE5502), 15 g of the conductive filler prepared in Example 1, 20 g of short fibers (silicate nano short fibers, 10 μm), and 10 g of coconut oil acid were mixed evenly, added to a screw extruder, extruded, and granulated at an extrusion temperature of 210° C. to obtain a mixture 1;
[0052] A2: 45 g of the conductive filler prepared in Example 1 and 105 g of HDPE (HDPE5502) were mixed evenly, added to a screw extruder, extruded and granulated at an extrusion temperature of 210° C., to obtain a mixture 2;
[0053] A3: 100g of mixed material 1 and 150g of mixed material 2 were mixed and injection molded. The temperature of each section of the injection molding machine was: the temperature of zone 1 was 190°C, the temperature of zone 2 was 200°C, and the temperature of zone 3 was 220°C; and a HDPE composite antistatic gasket was obtained.
[0054] Example 5
[0055] Compared with Example 4, Example 5 is a method in which only the conductive filler prepared in Example 1 added in Example 4 is replaced by the conductive filler prepared in Example 2 in equal amount, and the other components and preparation method are completely the same as those in Example 4.
[0056] Example 6
[0057] Compared with Example 4, Example 6 is a method in which only the conductive filler prepared in Example 1 added in Example 4 is replaced by the conductive filler prepared in Example 3 in equal amount, and the other components and preparation method are completely the same as those in Example 4.
[0058] Comparative Example 1
[0059] The preparation method of the conductive filler comprises the following steps:
[0060] S1: In a nitrogen atmosphere, 100 g of 1,3,5-triethynylbenzene, 180 g of 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), 30 g of tetrakis(triphenylphosphine)palladium(0), 10 g of cuprous iodide(Ⅰ), 5000 mL of triethylamine and 5000 mL of N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 75°C, the reaction was kept warm for 60 h, and the mixture was washed and dried to obtain component 1;
[0061] S2: Add 100g of component 1, 60g of iodobenzene diacetate, 35mL of benzonitrile and 1000mL of dichloromethane into reactor B and disperse them evenly. Control the temperature to 75°C, keep the temperature for 36 hours, wash and dry to obtain the washed substance. Mix the washed substance with KOH in a mass ratio of 1:3 and grind it into a quartz boat. In a nitrogen-filled tubular furnace, heat it at a rate of 5°C / min to 600°C and keep the temperature for 3 hours. Wash and dry to obtain component 2.
[0062] S3: Add 100g of component 2, 25g of hydroxylamine hydrochloride, 4g of triethylamine and 2000mL of anhydrous ethanol into reactor C and disperse them evenly. Control the temperature at 65°C and keep the reaction warm for 36h. Remove the ethanol by rotary evaporation. Add dichloromethane and water for liquid extraction. Remove the dichloromethane by vacuum distillation and dry to obtain a conductive filler.
[0063] Comparative Example 2
[0064] The preparation method of the conductive filler comprises the following steps:
[0065] S1: In a nitrogen atmosphere, 100 g of 1,3,5-triethynylbenzene, 180 g of 2,5-dibromo-1,4-difluorobenzene (CAS: 327-51-5), 30 g of tetrakis(triphenylphosphine)palladium(0), 10 g of cuprous iodide(Ⅰ), 5000 mL of triethylamine and 5000 mL of N,N-dimethylformamide were added to a reaction flask A, the temperature was raised to 75°C, the reaction was kept warm for 60 h, and the mixture was washed and dried to obtain component 1;
[0066] S2: Add 100g of component 1, 60g of iodobenzene diacetate, 35mL of benzonitrile and 1000mL of dichloromethane into reactor B and disperse them evenly. Control the temperature to 75°C, keep warm for 36h, wash and dry to obtain the washed substance. Mix the washed substance with KOH in a mass ratio of 1:3, grind it and put it into a quartz boat. In a tubular furnace filled with nitrogen, heat it at a rate of 5°C / min to 600°C and keep warm for 3h. Wash and dry it to obtain a conductive filler.
[0067] Comparative Example 3
[0068] Compared with Example 4, Comparative Example 3 is that only the conductive filler prepared in Example 1 added in Example 4 is replaced by the conductive filler prepared in Comparative Example 1 in equal amount, and the other components and preparation method are completely consistent with Example 4.
[0069] Comparative Example 4
[0070] Compared with Example 4, Comparative Example 4 is that only the conductive filler prepared in Example 1 added in Example 4 is replaced by the conductive filler prepared in Comparative Example 2 in equal amount, and the other components and preparation method are completely consistent with Example 4.
[0071] Comparative Example 5
[0072] Compared with Example 4, in Comparative Example 5, only the conductive filler prepared in Example 1 added in Example 4 is replaced with conductive carbon black in equal amount, and the other components and preparation method are completely consistent with Example 4.
[0073] Performance Testing
[0074] (1) Tensile strength: According to GB / T 1040-1992, the test was carried out using a universal material testing machine at a tensile speed of 30 mm / min. The tensile strength was calculated according to the following formula:
[0075] σt=p / (bd)
[0076] Wherein, σt-tensile strength, MPa; P-maximum load, N; b-specimen width, mm; d-specimen thickness, mm; the test results are shown in Table 1;
[0077] (2) Notched impact strength: According to GB / T 1043-70, a liquid crystal plastic pendulum cantilever beam impact tester is used to test the V-notched specimen. The maximum impact energy is 4 J, and the impact strength α is calculated according to the following formula:
[0078] α=[A / (bd)]×10 3
[0079] Where, α-impact strength, kJ / m 2 ; A-impact energy absorbed by the sample, J; b-remaining width of the sample, mm; d-thickness of the sample, mm; the test results are shown in Table 1;
[0080] (3) Surface resistivity and volume resistivity: According to GB / T 1944-1970, a ZC36 vibrating capacitance ultra-high resistance meter was used, the test voltage was 1000 V, the sample diameter was 100 mm, and the thickness was 4 mm; the test environment was 25±2°C and the relative humidity was 65±5%, and the surface resistivity and volume resistivity of the sample were tested; the test results are shown in Table 1;
[0081] Table 1: Statistical table of performance test data of Examples 4-6 and Comparative Examples 2-5
[0082]
[0083]
[0084] It can be seen from Table 1 that the conductive filler prepared in the present application is added to the HDPE composite antistatic gasket, giving the gasket excellent antistatic properties and mechanical properties.
[0085] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A production process of HDPE composite antistatic gasket, characterized in that: The steps include: A1: HDPE, conductive filler, short fiber and coconut acid are mixed evenly and added into a screw extruder for extrusion and granulation to obtain a mixture 1; A2: The conductive filler and HDPE are mixed evenly and then added into a screw extruder for extrusion and granulation to obtain a mixture II; A3: Mixing the mixture 1 and the mixture 2, and injection molding to obtain a HDPE composite antistatic gasket; The preparation method of the conductive filler comprises the following steps: S1: In a nitrogen atmosphere, add 1,3,5-triethynylbenzene, 1,4-dibromo-2,5-difluorobenzene, tetrakis(triphenylphosphine)palladium(0), cuprous iodide(I), triethylamine and N,N-dimethylformamide into a reaction flask A, heat to 70-80°C, keep the temperature for reaction for 48-72h, wash and dry to obtain component 1; S2: Add component 1, iodobenzene diacetate, phthalonitrile and dichloromethane into reactor B and disperse evenly, control the temperature to 70-80°C, keep warm for 24-48h, wash, dry and calcine to obtain component 2; S3: Add component 2, hydroxylamine hydrochloride, triethylamine and anhydrous ethanol into reactor C and disperse them evenly. Control the temperature at 60-70°C, keep the temperature for reaction for 24-48 hours, remove ethanol by rotary evaporation, add dichloromethane and water for liquid extraction, remove dichloromethane by vacuum distillation, and dry to obtain component 3; S4: Add component three, sodium hydroxide aqueous solution, 1,3-propane sultone and 1,4-dioxane into reaction kettle D, stir at room temperature for 12-18 hours, wash with acetone, and obtain a conductive filler.
2. A production process of HDPE composite antistatic gasket according to claim 1, characterized in that: Mixture 1 includes the following raw materials in weight percentage: 15-25% conductive filler, 15-20% short fiber, 5-10% coconut oil acid, and the balance is HDPE, and the sum of the weight percentages of the raw material components is 100%; the short fiber is silicate nano short fiber.
3. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: Mixture 2 includes the following raw materials in weight percentage: 30-40% conductive filler, 60-70% HDPE, and the sum of the weight percentages of the raw material components is 100%.
4. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The mass ratio of mixture 1 to mixture 2 is 1:1-1.
5.
5. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The addition ratio of 1,3,5-triethynylbenzene, 1,4-dibromo-2,5-difluorobenzene (CAS: 327-51-5), tetrakis(triphenylphosphine)palladium(0), cuprous(I) iodide, triethylamine, and N,N-dimethylformamide in S1 is 1 g: 1.5-2 g: 0.2-0.4 g: 0.05-0.15 g: 50-100 mL: 50-100 mL.
6. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The addition ratio of component 1, iodobenzene diacetate, phthalonitrile, and dichloromethane in S2 is 1 g: 0.4-0.8 g: 0.2-0.5 mL: 10-50 mL.
7. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The addition ratio of component 2, hydroxylamine hydrochloride, triethylamine and anhydrous ethanol in S3 is 1g: 0.2-0.3g: 0.03-0.05g: 10-50mL.
8. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The sodium hydroxide aqueous solution in S4 is 0.8-1g / mL sodium hydroxide aqueous solution; the addition ratio of component three, sodium hydroxide aqueous solution, 1,3-propane sultone, and 1,4-dioxane is 1g:7-15mL:2-3g:10-20g.
9. The production process of a HDPE composite antistatic gasket according to claim 1, characterized in that: The extrusion temperature in A1 is 200-210°C; the extrusion temperature in A2 is 200-210°C; the temperatures of each section of the injection molding machine in A3 are: zone 1 temperature 190-200°C, zone 2 temperature 200-210°C, zone 3 temperature 210-220°C.
Citation Information
Patent Citations
Side chain sulfonated polyimide / perfluorosulfonic acid composite membrane, preparation method and application thereof
CN108428837A
Conjugated microporous polymer and preparation method and application thereof
CN112403446A